Hatching of Globodera pallida Induced by Root Exudates Is Not Influenced by Soil Microbiota Composition - Gautier, Camille; Martinez, Lisa; Fournet, Sylvain; Montarry, Josselin; Yvin, Jean-Claude; Nguema-Ona, Eric; Guillerm-Erckelboudt, Anne-Yvonne; Piriou, Christophe; Linglin, Juliette; Mougel, Christophe; Lebreton, Lionel (Frontiers in Microbiology, 2020)
Plant-parasitic nematodes are among the most harmful pests of cultivated crops causing important economic losses. The ban of chemical nematicides requires the development of alternative agroecological approaches to protect crops against nematodes. For cyst nematodes, egg hatching is stimulated by host plant root exudates. Inducing “suicide hatching” of nematode second-stage juveniles (J2), using root exudates in the absence of the host plant, may constitute an effective and innovative biocontrol method to control cyst nematodes. However, before considering the development of this approach, understanding the effect of soil biotic component on cyst nematode hatching by root exudates is a major issue. The effectiveness of this approach could be modulated by other soil organisms consuming root exudates for growth as soil microbiota, and this must be evaluated. To do that, four different native agricultural soils were selected based on their physicochemical properties and their microbiota composition were characterized by rDNA metabarcoding. To disentangle the effect of microbiota from that of soil on hatching, four recolonized artificial soils were obtained by inoculating a common sterile soil matrix with the microbiota proceeding from each agricultural soil. Each soil was then inoculated with cysts of the potato cyst nematode, Globodera pallida, and low or high doses of potato root exudates were applied. After 40 days, viable J2 remaining in cysts were counted to determine the efficiency of root exudates to stimulate hatching in different soils. Results showed that i) when physicochemical and microbiota compositions varied among native soils, the hatching rates remained very high albeit small differences were measured and no dose effect was detected and ii) when only microbiota composition varied among recolonized soils, the hatching rates were also high at the highest dose of potato root exudates, but a strong dose effect was highlighted. This study shows that abiotic and biotic factors may not compromise the development of methods based on suicide hatching of cyst nematodes, using root exudates, molecules inducing J2 hatch or trap crops.